Dampak Pendapatan Asli Daerah Terhadap Belanja Langsung Kabupaten Bandung Barat - Chaereyranba Sholeh (Department of Public Administration, 2019)
This study has purpose to determine how the effect Regional Original Income to Direct Expenditures in West Bandung Regency for the period 2008-2017. This study uses the theory from Siregar (2015: 31) with method uses an associative type with a quantitative approach. This reseach useing secondary data with data collection techniques are literature studies (documentation) and field studies (observation). The population and sample of the study are the West Bandung Regency Regional Budget Realization Report 2008-2017. Statistical testing uses multiple regression analysis it where to determine how much influence the PAD component has on Direct Spending with a significance level of α = 0.05 using the t-test with SPSS 20 program. Significant value for the influence of independent variables regional tax, regional retribution, separated regional wealth management results and other legitimate PAD which is Regional Original Income simultaneously to Direct Expenditures of 0,000 <0.05 and calculated F value of 68,983> F table of 4, 53. So that can be concluded of the independent variable namely Regional Original Income simultaneously influences the dependent variable of Direct Shopping in West Bandung Regency. The results is calculation of the determination coefficient and correlation coefficient that the effect of Regional Original Income on Direct Spending is 98.2% with a correlation level of 0.982 which means it belongs to the category of very strong relationships. And the remaining 1.8% are influenced cause other variables not explained by the researcher.